Indeterminação: o acaso e o aleatório na música do século XX - Terra, Vera Regina Rebello (1999)
This work accomplishes an analysis of indeterminacy in twentieth century music, approaching the esthetical principles on which it is founded, the different nomenclatures used to designate them, and changes it produces on concepts of musical form and work as well as sound notation. Two opposite trends in such contemporary musical esthetics are focused, that is, aleatory music and chance music, here respectively represented by Pierre Boulez's and John Cage's poetics. Differing one from the other by refusing or allowing the performer the right of taking part in work's construction, traditionally regarded as a composer's attribute, their origin is refered to Anton Webern's serialism. The virtuality granted to the series in Anton Webern's music is enlarged in these esthetics to syntactical and morphological levels through the employment of indeterminate elements in compositional procedures. This way, indeterminacy inaugurates the research of open forms, which are configurated as a field of possibilities, instead of being experienced by the listener as well-shaped and accomplished works of art. White refusing tonal organization, which is based on the concept of causality, these esthetics propose a complex order, sharing new paradigms proposed by science and philosophy of this century